Disrupted superior collicular activity may reveal cervical dystonia disease pathomechanisms. Issue 1 (December 2017) - Govern, Eavan; Killian, Owen; Narasimham, Shruti; Quinlivan, Brendan; Butler, John; Beck, Rebecca; Beiser, Ines; Williams, Laura; Killeen, Ronan; Farrell, Michael; O'Riordan, Sean; Reilly, Richard; et al.
Abstract Cervical dystonia is a common neurological movement disorder characterised by muscle contractions causing abnormal movements and postures affecting the head and neck. The neural networks underpinning this condition are incompletely understood. While animal models suggest a role for the superior colliculus in its pathophysiology, this link has yet to be established in humans. The present experiment was designed to test the hypothesis that disrupted superior collicular processing is evident in affected patients and in relatives harbouring a disease-specific endophenotype (abnormal temporal discrimination). The study participants were 16 cervical dystonia patients, 16 unaffected first-degree relatives with abnormal temporal discrimination, 16 unaffected first-degree relatives with normal temporal discrimination and 16 healthy controls. The response of participant's superior colliculi to looming stimuli was assessed by functional magnetic resonance imaging. Cervical dystonia patients and relatives with abnormal temporal discrimination demonstrated (i) significantly reduced superior collicular activation for whole brain and region of interest analysis; (ii) a statistically significant negative correlation between temporal discrimination threshold and superior collicular peak values. Our results support the hypothesis that disrupted superior collicular processing is involved in the pathogenesis of cervical dystonia. These findings, which align with animal models of cervical dystonia, shed new light on pathomechanisms in humans.